2020
DOI: 10.2147/ijwh.s248240
|View full text |Cite
|
Sign up to set email alerts
|

<p>When Women Deliver at Home Without a Skilled Birth Attendant: A Qualitative Study on the Role of Health Care Systems in the Increasing Home Births Among Rural Women in Southwestern Uganda</p>

Abstract: Background: Uganda's maternal mortality remains unacceptably high, with thousands of women and newborns still dying of preventable deaths from pregnancy and childbirth-related complications. Globally, Antenatal care (ANC) attendance has been associated with improved rates of skilled births. However, despite the fact that over 95% of women in Uganda attend at least one ANC, over 30% of women still deliver at home alone, or in the presence of an unskilled birth attendant, with many choosing to come to hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…In addition, 5 key HCPs (2 senior obstetricians—a man aged 44 years and a woman aged 39 years—and 3 experienced female midwives aged 27, 38, and 55 years) were also purposively identified and interviewed during the formative phase. Detailed preliminary findings of these interviews have been documented elsewhere [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, 5 key HCPs (2 senior obstetricians—a man aged 44 years and a woman aged 39 years—and 3 experienced female midwives aged 27, 38, and 55 years) were also purposively identified and interviewed during the formative phase. Detailed preliminary findings of these interviews have been documented elsewhere [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…All messages included both prevention and promotional information. Additional data from the formative interviews on barriers to, and facilitators of, ANC attendance and skilled delivery had been already documented [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the present study showed that women living in rural areas are more likely to have home births, which is consistent with a recent systematic review (24). One possible explanation lies in the fact that pregnant women in rural areas feel fear that their privacy and traditions are not going to be respected in health facilities, and some indicated that they were afraid of being victims of abuse by health professionals (25)(26)(27), which highlights the marked gap between the rural population and health care.…”
Section: Discussionmentioning
confidence: 99%